International waters: Identifying basins at risk - Wolf, Aaron T.; Yoffe, Shira B.; Giordano, Mark (IWA Publishing, 2003)
Despite the growing literature on water and conflict in international river basins, little empirical work has been done to bolster common conclusions which are so widely reported. In order to address this gap, we set out to assess all reported events of either conflict or cooperation between nations over water resources during the last 50 years and to use these events to inform the identification of basins at greatest risk of political stress in the near future (5-10 years). The study is divided into three components:Compilation and assessment of relevant biophysical, socio-economic and geopolitical data in a global Geographic Information System (GIS), and use of these factors to determine history-based indicators for future tensions along international waterways.Using these indicators, identification of basins at risk for the coming decade.Identification and assessment of the potential for mitigating factors and new technologies resulting in a future different than that predicted by history-based indicators.In general, we find that most of the parameters regularly identified as indicators of water conflict are actually only weakly linked to disputes, but that institutional capacity within a basin, whether defined as water management bodies or treaties, or generally positive international relations are as important, if not more so, than the physical aspects of a system. It turns out then that very rapid changes, either on the institutional side or in the physical system, which outpace the institutional capacity to absorb that change, are at the root of most water conflict, as reflected in two sets of indicators: 1) “internationalized” basins, i.e. basins which include the management structures of newly independent states, and 2) basins which include unilateral development projects and the absence of cooperative regimes. By taking our parameters of rapid change as indicators-internationalized basins and major planned projects in hostile and/or institution-less basins-we are able to identify the basins with settings which suggest the potential for political stresses in the coming five to ten years. These basins include: the Ganges-Brahmaputra, Han, Incomati, Kunene, Kura-Araks, Lake Chad, La Plata, Lempa, Limpopo, Mekong, Ob (Ertis), Okavango, Orange, Salween, Senegal, Tumen and Zambezi.We then identify “red flags,” or markers related to these indicators, which might be monitored in the future. Finally, recognizing that history-based indicators may lose validity over time in a rapidly changing world, we ask, “what about the future, which may look nothing like the past,” and focus on four topics: new technologies for negotiation and management; globalization, privatization and the WTO; the geopolitics of desalination; and the changing sources of water and the changing nature of conflict.